Nitric Oxide Signaling and Sensing in Age-Related Diseases - Olga Mazuryk; Ilona Gurgul; Maria Oszajca; Justyna Polaczek; Konrad Kieca; Ewelina Bieszczad-Żak; Tobiasz Martyka; Grażyna Stochel (MDPI AG, 2024)
Nitric oxide (NO) is a key signaling molecule involved in numerous physiological and pathological processes within the human body. This review specifically examines the involvement of NO in age-related diseases, focusing on the cardiovascular, nervous, and immune systems. The discussion delves into the mechanisms of NO signaling in these diseases, emphasizing the post-translational modifications of involved proteins, such as S-nitrosation and nitration. The review also covers the dual nature of NO, highlighting both its protective and harmful effects, determined by concentration, location, and timing. Additionally, potential therapies that modulate NO signaling, including the use of NO donors and nitric oxide synthases (NOSs) inhibitors in the treatment of cardiovascular, neurodegenerative, and oncological diseases, are analyzed. Particular attention is paid to the methods for the determination of NO and its derivatives in the context of illness diagnosis and monitoring. The review underscores the complexity and dual role of NO in maintaining cellular balance and suggests areas for future research in developing new therapeutic strategies.